Intentions And Motive In Augustine’s Just War Teaching - Petrus Farneubun (Jurnal Ilmiah Hubungan Internasional, 2014)
Abstract: Augustine, one of the greatest christian thinkers, tries to reconcile the love of neighborsand justification of wars. He develops a radically different biblical interpretation than those of earlyChurch Fathers who believe in incompatibility of Jesus's central teaching of loving neighbour andChristian participation in warfare. Augustine repudiates such incompatibility. This paper investigatesthe teaching of Augustine's just war teaching formulated in his masterpiece The City of God. In thelight of this tradition, this paper specifically adresses the intentions and the primary motive of the justwar. This paper argues that both the intentions and motive have to be distinctive. Accordingly, war isjustified if it meets two distinctive conditions. First, the goal of the war is to bring peace, restorejustice, and and punish wrong doers. Second, the war should be based on Christian charity or love ofneighbours. This paper begins by introducing the core issue of Christian understanding of its positionon warfare, followed by brief profile of Augustine. Then, it addresses Augustine's interpretation ofJesus' teaching and finally it analyses Augustine's just war teaching by focusing on intentions andmotive. Two cases, NATO Interventions in Kosovo 1999 and Libya 2011, are also included to illustratethe principle of Right Intention and Motive. It argues that NATO interventions meet the conditions ofRight Intention but fail in the principle of Right Motive.Key Words: Augustine, Just War, Love, Justice, Intentions, Motive